2014
DOI: 10.4067/s0301-732x2014000200014
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sildenafil therapy for pulmonary hypertension in dogs: a systematic review

Abstract: RESUMENEl objetivo de esta revisión sistemática fue evaluar la eficacia del sildenafil en el tratamiento de la hipertensión pulmonar (HP) en perros y, cuando posible, proponer recomendaciones a favor o en contra de su uso. Se realizaron búsquedas electrónicas en seis bases de datos internacionales. El criterio de inclusión fue estudios clínicos in vivo que evaluaron la eficacia del sildenafil en el tratamiento de la HP de origen natural. El sistema de clasificación se diseñó para considerar aspectos como la fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The target pulmonary vasodilating effect of sildenafil decreases the pulmonary pressure while having minimal effects on systemic blood pressure [44]. However, some studies have found that systemic blood pressure tended to decrease -remained within the normal range -after treatment with sildenafil [7,9,28].…”
Section: Discussionmentioning
confidence: 99%
“…The target pulmonary vasodilating effect of sildenafil decreases the pulmonary pressure while having minimal effects on systemic blood pressure [44]. However, some studies have found that systemic blood pressure tended to decrease -remained within the normal range -after treatment with sildenafil [7,9,28].…”
Section: Discussionmentioning
confidence: 99%
“…5 The most common current use of sildenafil in veterinary medicine is for treatment of pulmonary hypertension; adverse effects are uncommon at therapeutic dosages. 6 The use of sildenafil to aid in wound healing has been explored via several applications. Oral sildenafil has been shown to improve wound healing in rats, 7 skin flap survival in rats and pigs, 8,9 colonic anastomosis healing in rats, 10,11 and healing of open surgical wounds in dogs.…”
mentioning
confidence: 99%
“…Sildenafil has minimal systemic effects because it has a selective vasodilation effect in organs that have abundant phosphodiesterase-5 expression, such as lungs (Michelakis et al, 2002;Lepore et al, 2005b;Kellihan and Stepien, 2012). The adverse effects of sildenafil have rarely been reported in dogs (Silva et al, 2014). The present study showed no difference in complete blood counts and blood chemistry profile values between the placebo and sildenafil groups at day 7 and between day 0 and 7 of the sildenafil groups.…”
Section: Chapter V Discussionmentioning
confidence: 46%
“…The target pulmonary vasodilating effect of sildenafil decreases the pulmonary pressure with minimal effects on systemic blood pressure (Michelakis et al, 2002;Lepore et al, 2005a;Silva et al, 2014). However, some studies found that systemic blood pressure tended to decrease, but still within normal range after treatment with sildenafil (Bach et al, 2006;Kellum and Stepien, 2007;Brown et al, 2010).…”
Section: Chapter V Discussionmentioning
confidence: 99%